Experiences of physiotherapy residents in a burn treatment center of a trauma referral hospital: An experience report (Research, Society and Development, 2023)
To describe the experiences of physiotherapy residents from the Multiprofessional Residency Program (PRM) in Urgency and Emergency in Trauma during their first rotation at the Burn Treatment Center of a trauma referral hospital. This is a descriptive study with a narrative approach, of the Experience Report type, which discusses the experiences lived by the first-year residents together with the CTQ physiotherapists. The study was developed based on a description of the residents' experiences and a search of the LILACS, SCIELO, PubMed and Google Scholar databases in order to create a dialog between the practice experienced and that found in the literature. During their rotation at the CTQ, the residents were introduced to the sector's routine in order to gain a theoretical and practical understanding of the active search for hospitalized patients, the physiotherapeutic assessment of burn patients, as well as the development of goals and treatment plans for the preparation of ward and ICU procedures and the participation in surgeries and sedoanalgesia protocols. In this way, it can be seen that the inclusion of residents in a specialized treatment center allows for more targeted preparation in the training of specialists.